Cytomegalovirus-Immune Recovery Retinitis After Initiation of Highly Active Antiretroviral Therapy: A Case Series - Qian, Yiwen; Wang, Luoziyi; Jiang, Jing; Suo, Jinshan; Weng, Huan; Che, Xin; Lu, Hongzhou; Wang, Zhiliang (Frontiers in Medicine, 2022)
Purpose: To delineate the characteristics and treatment of cytomegalovirus-immune recovery retinitis (CMV-IRR) in human immunodeficiency virus (HIV) patients with immune recovery under effective highly active antiretroviral therapy (HAART) regimen. Methods：We reported four HIV patients who were diagnosed with CMV-IRR soon after effective HAART. Plasma levels of CD4 T cells, HAART regimen and other clinical and laboratory characteristics of the four patients were described. Patients were monitored for ocular manifestations and clinical signs under effective ocular and systemic anti- cytomegalovirus (CMV) and corticosteroid treatment for 12 months. Results：With HAART, plasma levels of CD4 T cell counts rose remarkably. The mean baseline CD4 count of the four patients was 14.5(range from7-33) cells/ul before HAART and 183.25(range from 153 to 220) cells/ul when diagnosed with CMV-IRR. Ophthalmic examination demonstrated severe vitreous opacities and necrotizing retinitis, intraretinal hemorrhages and vasculitis. A large number of CMV sequencing was detected by DNA sequencing of vitreous samples. All four patients were recovered from CMV-IRR with anti-CMV and corticosteroid treatment. Conclusions: CMV-IRR is a new diagnosis of HIV associated ocular complication under HAART. These findings suggest that the immunological effects of HAART may accelerate the CMV retinitis in patients with very low initial CD4 T cell counts. HIV patients are recommended to have a thorough fundus examination before HAART initiation and a close follow up especially in those with low CD4 counts to avoid the progression of CMV retinitis.